SECURE AUDIO STEGANOGRAPHY BY LSB FOR HIDING INFORMATION - Rupali Patil; Prof. Dipak Pawar (International Journal of Innovations in Engineering Research and Technology, 2021)
Steganographyis an art ofsending hidden data or secretmessages so that a third party cannot detect the presence of the secret messages. The goal of steganography is different from classical encryption. In this paper, secret message in the form of text file is embedded within the carrier audio file (.wav). The LSB embedding method replaces the LSB bits of carrier audio file by secret data bits. In the transmitter end the output is similar to the carrier with secret message embedded inside. At the receiver end the original message can be retrieved without any loss.